PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBASIS KOMPUTER UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TIK : STUDI KUASI EKSPERIMEN TERHADAP SISWA KELAS VII SEMESTER II DI SMP NEGERI 15 BANDUNG - Indikhiro Awalani, - (2010)
Reformation in learning is needed to be built and developed to create interactive learning environment between teacher and students. In this respect, students are demanded to play actively in learning process. But in the reality, there is still found many learning which is still conventional, where the learning is still dominated by teacher, while students tend to be silent and passively receive learning material. It cause low students' learning output. Therefore, it is needed a learning model which is appropriate. One of the learning models that can facilitate the problem is Computer Based Cooperative Integrated Reading and Composition (CIRC). The application of this model is aimed to 1) know the description of students' learning output improvement in cognitive domain towards TIK material after the application of computer based CIRC learning model, 2) know the effectiveness of computer based CIRC learning model towards TIK course. Method that is used in this study is experiment quasi method. Research data is collected through test instruments in the form of multiple choice items to measure students' learning output in cognitive domain and hypothesis testing is performed by using t test. This study result shows that students' learning output in cognitive domain has improved after the application of computer based CIRC learning model. This improvement is indicated from the average of students' grade in students' cognitive domain before learning is 23.67, and then improves to be 80.47. Besides, this study is also shows that computer based CIRC learning model is very effective to be applied in TIK learning. It can be seen from average normalized gain around 0.74.